Pediatric Inflammatory Multisystem Syndrome Temporally Associated with SARS-CoV-2 Treated with Tocilizumab - Niño-Taravilla, Carmen (Pediatr Rep, 2020)
We describe a case of Pediatric Inflammatory Multisystem Syndrome temporally associated with SARS-CoV-2 (PIMS-TS) in an 8-year-old child. The patient developed multiorgan dysfunction, including mixed shock, cardiac dysfunction with myocarditis, pneumonia, acute kidney failure, and gastrointestinal involvement characterized by inflammation of the wall of the bowel and pancreatitis. After treatment with Tocilizumab and corticoid therapy, he presented clinical improvement and normalization of inflammatory markers. PIMS-TS is a new disease developed in a small percentage of patients, so a high degree of suspicion is necessary to establish the diagnosis. Supportive care is of paramount importance. The use of Tocilizumab to control the inflammatory response is likely to be beneficial, but the best immunotherapeutic agent has not yet been established. Randomized clinical studies should be run to determine the best treatment.